Stress-Strain Relationship of Clay in Dongting Lake Area Based on Three Damage Factors. (20th April 2023) - Chen, Qiu-Nan; Xu, Xiao-Di; Yang, Zhen-Yu; Ma, Bin-Hui; Hu, Wei; He, Yong-Chao; Huang, Xiao-Cheng; Lei, Yong
Abstract : CU test and CD test were performed to capture the stress-strain characteristics of the clay in Dongting Lake area, China. Since the classical constitutive model cannot ideally describe the strain hardening behavior of the clay, an improved constitutive model that involved three damage factors was proposed. The damage first factor D 1, which represents elemental volume strength F, was fitted by the Weibull function. The second and third damage factors D 2 and D 3, which represent the porosity ratio e and the drainage rate P ε respectively, were fitted by Harris function. The CD test damage model is constructed by D 1, D 2, and D 3 . In the CU test, the porosity ratio e is a constant value, and the drainage volume is 0, so that D 2 is constant value and D 3 is 0. Therefore, the CU test damage model of the clay was constructed using the damage first factor D 1 . In the end, the accuracy of the proposed CU/CD damage constitutive models of the clay was validated with the experimental results. It is found that the results fitted by the proposed methodology are in good agreement with the experimental results.